Analisis Hukum Pemutusan Hubungan Kerja (PHK) terhadap Karyawan dalam Perusahaan dengan Alasan Disharmoni - Dwi Atmoko; Jantarda Mauli Hutagalung (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
The new regulations on the concept of layoffs (PHK) are perceived as increasingly critical and detrimental to some workers. While the old regulations were deemed non-binding, the new regulations reintroduce the issue of termination of employment due to disharmony within the company. This research, conducted normatively, analyzes how the concept of termination of employment (PHK) is defined in existing regulations and legislation. In this era of globalization, human resource issues within a company require greater attention. No matter how sophisticated the technology used in a company and how much capital is invested, it is ultimately the employees who will carry out the work. This demonstrates that without the support of high-quality employees in carrying out their duties, even with sophisticated capital and technology, it is impossible to achieve optimal results. Termination of employment due to disharmony is certainly not a valid reason, as employment regulations stipulate several conditions governing the termination of an employment contract.